Research productivity during PhD enrolment for New Zealand sociology 2010–19: latest decade output patterns by gender and university. (2nd October 2022) - Rajčan, Adam; Burns, Edgar A.
ABSTRACT: Sociology has come late to the practice of publishing during PhD enrolment. This contrasts to fields such as science disciplines (STEM) and psychology where publishing during PhD is part of the disciplinary culture. In New Zealand sociology, over the last decade, the traditional PhD monograph continues to be the main format. Closer measurement of academic research outputs by the New Zealand Performance-Based Research Fund (PBRF) creates new pressures in the oversupplied academic-research labour market. This study has three main findings. First, within the decade since the PBRF was introduced, the publishing patterns of sociology PhDs have changed very little on the surface. It should be noted, however, that more than half of these students successfully published at least one refereed output, suggesting a possible disciplinary shift in students attempting to produce publications during candidacy. Second, overall in this time period, men and women published during their PhD at equal rates. This, however, masks variation by the institution. Women outperformed men at all institutions except at the largest sociology programme, Auckland University, where they published at the same rate as men. Third, gender differences by quality, sociology versus non-sociology publications and by Australasian versus international publications showed no significant differences.